Jornal Folhinha Aplicada on-line: um exercício de autoria - Barbosa, Leonarlley Rodrigo Silva (2018)
It is widely known that most of the reading and writing practices at school occur based on the idea of language as communication, which significantly reduces the opportunity for students to fulfill reading and writing experiences in a more active and authorial way. To discuss this issue and present a proposal that would contribute to Portuguese language teaching at school, especially in the initial grades, encouraging student protagonism, were the objectives of this dissertation. Hence, it was decided to approach conceptions derived from the hypothesis of the Unconscious theoretically, as done by Freud and Lacan, in order to broaden the ideas of subject and language, as well as to defend an exercise of authorship. After all, a text, oral and/or written, carries the marks and effects of how each subject elaborates their encounter with the world. Thus, after a bibliographic study and usage of the digital technologies, it was possible to transform a printed student newspaper into a website, the Folhinha Aplicada. The result of this work is linked to the Departmento de Pedagogia of the Centro de Ensino e Pesquisa Aplicada à Educação of the Universidade Federal de Goiás as an extension project and to the research project Arte, psicanálise e educação: os procedimentos estéticos do cinema e as vicissitudes da infância. In the website format, the student newspaper became more accessible, interactive and obtained an official record. It is hoped that, in this way, it will contribute to promote more inclusive teaching experiences with possibilities to expand a student's self-assessment process, valuing its course through the school, not only regarding Portuguese language teaching, but other subjects as well. In addition, the exercise of acceptions it presents is valued, not as a final product, but as a process, so that the student can experience and discover. Finally, it is believed that the Folhinha Aplicada can contribute to further experiences with knowledge, with the other and with the world.